دراسة فعالية المركبات الكاروتينويدية المستخلصة من قشور الروبيان كمضادات أكسدة ومضادات ميكروبية في حفظ اللحوم: هيفاء علي عواد مازن جميل هندي - عواد هيفاء علي (Journal of Kerbala for Agricultural Sciences, 2017)
دراسة فعالية المركبات الكاروتينويدية المستخلصة من قشور الروبيان كمضادات أكسدة ومضادات ميكروبية في حفظ اللحوم هيفاء علي عواد مازن جميل هندي جامعة كربلاء / كلية الزراعة جامعة بغداد/ كلية الزراعة/قسم علوم الأغذية المستخلص أجريت الدراسة لغرض اختبار فعالية المركبات الكاروتينويدية المستخلصة من قشور الروبيان المحلي والمستحصل من الأسواق المحلية للأنواع Penaus emisulcats Penaus japonicas,و Exopalamon styliferus المشتراة من الأسواق المحلية في بغداد , وتقييم كفاءتها كمضادات للأكسدة و مضادات بكتيرية في حفظ لحوم البقر. أستخلصت الكاروتينويدات من قشور الروبيان المجففة بوساطة مزيج من المذيبات العضوية شملت هكسان : أسيتون (1 : 1 ح : ح) وأضيفت المستخلصات الكاروتينويدية إلى عينات من مفروم لحم البقر بمقدار 2 و4% فضلاٌ عن عينة مقارنة من دون أضافة وعينة أضيف لها مضاد الأكسدة التجارية Butylated hydroxyl toluin (BHT) بمقدار %0.02 . حفظت العينات في التبريد 4مْ لمدد 6 , 3 , 0 أيام . قدرت الفعالية المضادة للأكسدة للمستخلصات الكاروتينويدية بقياس رقم البيروكسيد PV)) Peroxide Value , وقيمة حامض الثايوباربيوترك Thiobarbituric acid TBA)) خلال مدة الخزن المبرد . أظهرت النتائج المستحصلة تفوق المعاملة المضاف لها المستخلص بمقدار 4% واستقرار قيم رقم البيروكسيد للعينات المحفوظة في التبريد بعد 6 أيام وبقاءه ضمن الحدود المقبولة للنوعية الصالحة للأستهلاك البشري إذ بلغت 7 مليمكافىْ/كغم زيت وبلغت قيم حامض TBA لنفس العينة 8.88 مالون الديهايد/كغم . أظهرت النتائج أن أضافة 4% من مستخلص الكاروتينويدات الى لحوم الأبقار المفرومة أدى الى أنخفاض العدد الكلي للبكتريا الهوائية وعدد بكتريا القولون وعدد البكتريا المحبة للبرودة من قيم بدائية 6x102 , 1.6 x105 , 4.6 x107 و.م.م/غم إلى1.5 x10 , 2 x10 , 3.8 x 106 و.م.م/غم على التوالي عند الخزن المبرد ( 4مْ ) لمدة 6 أيام. Study of the activity of carotenoids extracted from shrimps shell as antioxidant and antimicrobial in meat preservation H.A.Awad* M.J.Hindi University of kerbala / College of Agriculture |* University of Baghdad /College of Agriculture/ Dep. of Food Science Abstract This investigation was carried out to evaluate the activity of Carotenoids extracted from shrimp shell related to Penaus semisculcats , Penaus japonicas and Exopalamon styliferus that obtained from retail out in Baghdad – Iraq. The Carotenoids were extracted from dried shrimp's shell by organic solvents comprised of Hexane : Acetone ( 1: 1 , V : V( The antioxidant capacity of crude carotenoids extract was added seperately to minced beef at 2% and 4% , further samples contained the commericial antioxidant ( BHT) was added to aforementioned samples at 0.02% together with a blank specimen. Samples were refrigerated at 4 C° for 0 , 3 and 6 days. The antioxidant capacity of extract were assayed via Peroxide Value ( PV ), Thiobarbituric acid ( TBA ) , The obtained results revealed that beef samples with 4% carotenoides were superior as PV were stable after 6 days of storage at 4C°, with an acceptable value of 7 milliequi/kg oil , The TBA was 8.88 mg malonaldehyde/kg . The antimicrobial activities of crude carotenoides added to the samples above were also examined via assaying the Total bacterial Count ( TBC ) , Coliform Count ( CC) and Total Psychrotrophic Count ( TPC) . against three bacterial isolates and included Bacillus subtilis , Staphylococcus aureus and Pseudomonas aeruginosa . The obtained results revealed that 4% carotenoids extract added to minced beef reduced the bacterial growth as evaluated by TBC , CC and TPC from 6x102 , 1.6x105 and 4.6x107 cfu/g to reach 1.5x10 , 2x10 and 3.8x106 cFu/g respectively when stored at 4 C° for 6 days .